Phase Equilibria for Heterogeneous Azeotropic Distillation - Campanella, Enrique Angel (2008)
Heterogeneous azeotropic distillation is used for separating no ideal mixtures. The technique uses minimum-boiling azeotropes and liquid-liquid immiscibilities in combination to break the azeotropes or tangent pinches in the mixture that would prevent the desired separation. However, other configurations are possible. Azeotropic distillation processes are developed using residue curve maps to explain the behavior of entire systems of heterogeneous azeotropic distillation columns as well as the individual columns that make up the system (Pham and Doherty 1990a, 1990b, 1990c). This conceptual design is a starting point to most rigorous design. Nevertheless, to generate a good conceptual design it is necessary to have a no ideal solution model capable of predicting vapor-liquid equilibrium, liquid-liquid equilibrium, vapor-liquid-liquid equilibrium, homogeneous and heterogeneous azeotropic points (Cairns and Furzer, 1990). Recently, a surprising feature of azeotropic distillation columns, multiple steady states, was discovered. It refers to output multiplicities, that is, that a column of a given design exhibits different columns profiles at steady state for the set of inputs and the same values of the operating parameters. This aspect, multiple steady states (MSS), should be studied with azeotropic distillation simulation. In this paper we discuss a recommendation to correlate heterogeneous azeotropic ternary system. The reability of the use of the recommended correlation is analyzed through heterogeneous azeotropic distillation.